The record of sea water chemistry evolution during the Ediacaran–Cambrian from early marine cements - Yi Xiong; Rachel Wood; Laetitia Pichevin (The Depositional Record, 2023)
Abstract The Ediacaran–Cambrian Radiation marks the widespread appearance of metazoans and calcareous biomineralised hard parts. These innovations occurred during an interval of dynamic changes in marine redox and sea water chemistry. Here, changing carbonate mineralogy, Mg/Ca ratios and rare earth element concentrations including the relative abundance of cerium (Ce anomaly: Ceanom) are documented to track sea water oxygen levels, in well‐preserved early marine cements from shallow marine reefs from Cambrian Stages 2–4 (ca 525–512 Ma). First, integrating the mineralogical data with published records, several shifts in dominant carbonate mineralogy are inferred: ‘dolomite‐aragonite seas’ in the late Ediacaran; ‘aragonite/high‐Mg calcite seas’ in Cambrian Stage 2; a temporary shift to a ‘calcite sea’ during early Cambrian Stage 3; an ‘aragonite sea’ between late Cambrian Stage 3 and late Cambrian Stage 4, then a gradual shift from mixed ‘aragonite–calcite seas’ during the middle and upper Cambrian towards a ‘calcite sea’ by the early Ordovician. Second, based on measured mMg/Ca in early marine cements, calculated sea water mMg/Ca at 15 and 35°C ranges from 1.2 to 0.8 in Cambrian Stage 2, 0.7–0.4 in Stage 3 and 1.4–0.9 in Stage 4 respectively. Finally, analysed Ceanom data combined with existing Ceanom data suggest potentially three phases of global oxic expansion. First, a long‐lived phase of progressive oxygenation during the late Ediacaran to Fortunian (ca 550–540 Ma; average Ceanom from 0.99 to 0.41), and possibly two shorter phases during early Cambrian Stage 3 (ca 519 Ma; average Ceanom from 0.91 to 0.40) and Stage 4 (ca 512 Ma; average Ceanom from 1.02 to 0.49), bounded by intervals of more dominant anoxia. Summarising, these data demonstrate that early marine cements offer an underused and high‐resolution archive of shallow marine redox and sea water chemistry through this critical transition in Earth's evolution.